Effect of aromatherapy on dental patient anxiety: A randomized controlled trial - M Venkataramana; K.V. N. R. Pratap; Madhavi Padma; Siva Kalyan; A Anitha Reddy; Pavana Sandhya (Wolters Kluwer Medknow Publications, 2016)
Introduction: Dental anxiety is a common and potentially distressing problem, both for the patients and for dental practitioners. It is considered to be the main barrier and affects the working lives of dental professional potentially compromising their performance. Aim: To know the effect of aromatherapy in the reduction of dental anxiety and to compare the anxiety levels of dental patients with the control group. Materials and Methods: A randomized controlled trial design was used. Of 40 dental clinics in Khammam town, 10 dental clinics were selected by simple random sampling method. A total of 100 patients attending the dental clinic for the first time were included in the study. Ambient odor of lavender was maintained with a candle warmer. A questionnaire comprising demographic information, smoking status, Modified dental anxiety scale (Humphries et al. in 1995), was given to the patients when they were waiting in the waiting room. Student's t-test and ANOVA test were used for data analysis. The level of significance was set at 0.05. Results: Considerable decrease in anxiety scores in 3 age groups was observed. A statistically significant (P = 0.002) decrease with age in mean anxiety score. A significant difference in anxiety scores of lavender group, a significant decrease of anxiety scores with an increase of age. Conclusion: Lavender decreased the current anxiety scores of patients effectively.